Larvicidal Activity of Plant and Algae Extracts, Essential Oils and Isolated Chemical Constituents against Aedes aegypti - M. do A.F. Navarro, Daniela; C.B. da Silva, Patrícia; F.R. da Silva, Marcelo; H. Napoleao, Thiago; M.G. Paiva, Patrícia (Natural Products Journal, The, 2013)
Aedes aegypti is vector of Dengue and Yellow Fevers, a mosquito of public health importance. It is the most broadly disseminated urban species of mosquito in the world. Larval insecticide is one of the alternatives to control the mosquito dissemination. Temephos and Bacillus turinghiensis subsp. israelensis (Bti) are the larvicidal most used in the world to combat A. aegypti mosquito. In face of larvae resistance to Temephos and the high cost of Bti production in large scale, research programs on insecticides often focus on alternative compounds and natural products as rich sources of larvicides. In this work we describe significant larvicidal activity research of plant and algae extracts, essential oils and isolated compounds against A. aegypti.
Keywords: larvicidal activity